Optimalisasi Pengelolaan Zakat Produktif untuk Pemberdayaan Ekonomi Umat - Fahri Eka Jaya; Moh Muksit (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
Zakat has great potential in improving the welfare of the people through economic empowerment. This research aims to explore the optimization of productive zakat management in the context of economic empowerment of the people in Indonesia. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. This research involves mustahik as respondents to understand their experiences and perspectives related to productive zakat management. The results of the activity showed that the productive zakat-based empowerment program, which includes entrepreneurship training, financial literacy, and the provision of business capital, succeeded in increasing economic independence by 70% mustahik. In addition, 85% of businesses supported by productive zakat remained stable after six months, reflecting the program's success in creating sustainable change. The implications of this activity show that more productive and sustainable management of zakat can increase public trust in zakat institutions, as well as encourage more muzakki participation. This study recommends the development of more integrated empowerment programs and effective monitoring systems to ensure the long-term impact of productive zakat. Thus, zakat can function not only as an instrument of wealth redistribution, but also as a significant tool of economic empowerment.